DNA Isolation Technique of Clove Plant Genomes Using Buffer CTAB Modification - Sundari Sundari (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2018)
The simple and efficient method for genomic DNA isolation protochol from clove, its woody crops containing high polysaccharide and phenol levels has been described here. In the present study, using modified CTAB for plant DNA isolation method were studied for removing the highly concentrated polysaccharides from genomic DNA of woody crops.This method involves the modified CTAB   at the pvp concentration, time incubate  and precipitate procedure employing DNA purification  step to remove polysaccharides and phenol residu.  Compared with the two studied DNA isolation methode of clove using standart CTAB and modified CTAB the everage yield high quality DNA whole genom is 1.90 purity and DNA was suitable for PCR and RAPD analyses.